Decreasing Tumor Growth and Angiogenesis by Inhibition of Coagulation - Nadir, Yona (Seminars in Thrombosis and Hemostasis, 2019)
Data regarding the effect of coagulation proteins on enhancing angiogenesis and tumor growth are ample. Thus, inhibition of the coagulation system in an attempt to reduce tumor growth and metastasis seems appealing. However, such molecules as direct oral anticoagulants, warfarin and heparins, may impose a bleeding tendency, limiting the treatment dose that can be used. The heparanase protein, as a cofactor for tissue factor (TF) activity, enhances activation of the coagulation system and in addition has several nonhemostatic effects increasing tumor growth. The molecules currently investigated in the field of cancer and coagulation are heparin mimetics and inhibitors of heparanase derived from TF pathway inhibitor 2. Both groups of molecules are inhibitors of heparanase and in addition pose a low bleeding tendency. Hence, interfering in heparanase activity seems to be a promising target for development of antitumor drugs.
Keywords: cancer; coagulation; heparanase; heparins; TFPI-2 peptides